The immune exhaustion paradox: activated functionality during chronic bacterial infections - María L Ruiz-de la Cruz; Mario César Salinas-Carmona (Journal of Infection in Developing Countries)
Co-inhibitory molecules, such as cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1), known as immune checkpoints, regulate the activity of T and myeloid cells during chronic viral infections and are well-established for their roles in cancer therapy. However, their involvement in chronic bacterial infections, particularly those caused by pathogens endemic to developing countries, such as Mycobacterium tuberculosis (Mtb), remains incompletely understood.